The State Intervention in the Islamic Education in Aceh: Threats or Opportunities? - Mujiburrahman, Mujiburrahman; Zulfikar, Teuku; Ahmad, Shukri; Melayu, Hasnul Arifin; Jasafat, Jasafat (SCAD Independent, 2024)
The enactment of the Aceh Governance Law (UUPA) allows the state’s intervention to the nature of Islamic boarding schools in Aceh, which is originally connected to Aceh’s socio-cultural system into the formality of the State’s administrative structure. This article utilized a triangulation methodology, which involved the integration of document analysis, observation, and in-depth interviews. The study generated data from participants located within the dayah, including 2 teungku chik (leadership), 2 teachers, and 5 students; and participants located outside the dayah, including 2 academics, 2 social figures, and a director of Department of Dayah Education. The findings of our study indicated that the institutional frameworks of dayah had undergone modernization, with significant improvements in infrastructure, integration of curricula, enhancement of human resources (teungku-teacher and santri-student), and expansion of collaborations and networks. This modification granted the dayah of Aceh a more favorable standing within the Acehnese social hierarchy. This study highlighted that dayah institutions retained their cultural foundation as centers of Islamic instruction despite the changes they experienced. Instead, the incorporation of State action has led to the establishment of institutional and intellectual prosperity; it appeared that state intervention was more of an opportunity than a threat.